1976
DOI: 10.1111/j.1432-1033.1976.tb10351.x
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐State Kinetic Studies of the Synthesis of Indoleglycerol Phosphate Catalyzed by the α Subunit of Tryptophan Synthase from Escherichia coli

Abstract: For the a subunit of tryptophan synthase and at constant concentration of D-glyceraldehyde 3-phosphate the saturation curves with respect to indole concentration are weakly sigmoidal. This phenomenon can be explained by interaction between indole bound to the effector site established previously and the active center of the monomeric a subunit. Kinetic studies of the inhibition of indoleglycerol phosphate synthesis by the analogue indolepropanol phosphate show that the inhibition is competitive with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The value suggests that the transition rate may be decreased by several orders of magnitude in the isolated α–monomer but reduced only a little in the isolated β–monomer. The results are in good agreement with experiments showing that the catalytic rate is ∼100 times slower in the isolated α–monomer but only 1.5 times slower in the isolated β–monomer as compared with the αββα tetramer [28][29]. The calculation further supports our conjecture that one major role of oligomerization in TRPS is to help the ligand binding processes.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The value suggests that the transition rate may be decreased by several orders of magnitude in the isolated α–monomer but reduced only a little in the isolated β–monomer. The results are in good agreement with experiments showing that the catalytic rate is ∼100 times slower in the isolated α–monomer but only 1.5 times slower in the isolated β–monomer as compared with the αββα tetramer [28][29]. The calculation further supports our conjecture that one major role of oligomerization in TRPS is to help the ligand binding processes.…”
Section: Resultssupporting
confidence: 90%
“…Steady–state kinetic studies [28] revealed that the rate of the α–reaction in the isolated α–subunit is ∼100 times slower than that in the αββα tetramer of Escherichia coli TRPS, which has 84% identities and 94% similarities with the Salmonella typhimurium TRPS used in our simulation studies. This observation reflects a strong synergistic effect of subunits on the α–catalysis in the multi-enzyme complex.…”
Section: Introductionmentioning
confidence: 96%
“…TrpA_1-2 has the highest k cat /K M PRA value of all analysed variants (Table III). We tested whether this variant is still able to catalyse the reverse TrpA reaction (synthesis of IGP from indole and D-glyceraldehyde 3-phosphate) (Weischet and Kirschner, 1976), which is thermodynamically preferred to the physiological reaction (Fig. 1).…”
Section: Trpf Activities Of Purified Trpa Variantsmentioning
confidence: 99%
“…indole and G3P react to form IGP). It should be noted that the catalytic activity of the free αTS enzyme is lower than when in found in complex with the βTS subunit . The T183V substitution also led to a substantial decrease in k cat , but had little effect on the K M for indole or G3P (Table ).…”
Section: Resuls and Discussionmentioning
confidence: 94%